Virulence phenotypes result from interactions between pathogen ploidy and genetic background - Feistel, Dorian J. (Ecol Evol, 2020)
Studying fungal virulence is often challenging and frequently depends on many contexts, including host immune status and pathogen genetic background. However, the role of ploidy has often been overlooked when studying virulence in eukaryotic pathogens. Since fungal pathogens, including the human opportunistic pathogen Candida albicans, can display extensive ploidy variation, assessing how ploidy impacts virulence has important clinical relevance. As an opportunistic pathogen, C. albicans causes nonlethal, superficial infections in healthy individuals, but life‐threatening bloodstream infections in individuals with compromised immune function. Here, we determined how both ploidy and genetic background of C. albicans impacts virulence phenotypes in healthy and immunocompromised nematode hosts by characterizing virulence phenotypes in four near‐isogenic diploid and tetraploid pairs of strains, which included both laboratory and clinical genetic backgrounds. We found that C. albicans infections decreased host survival and negatively impacted host reproduction, and we leveraged these two measures to survey both lethal and nonlethal virulence phenotypes across the multiple C. albicans strains. In this study, we found that regardless of pathogen ploidy or genetic background, immunocompromised hosts were susceptible to fungal infection compared to healthy hosts. Furthermore, for each host context, we found a significant interaction between C. albicans genetic background and ploidy on virulence phenotypes, but no global differences between diploid and tetraploid pathogens were observed.